Analyse spatiale et criminologie - Élie, Daniel (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1994)
This article addresses the spatial analysis of crime. Following a brief historical overview, the author discusses major conceptual and methodological issues relating to the study of space and crime. Emphasis is placed on the description of spatial statistical tools (i.e. spatial mean, standard distance, turbulence...) and on the problem of spatial autocorrection. Two maps are presented and discussed.